1996
DOI: 10.1055/s-2007-1011999
|View full text |Cite
|
Sign up to set email alerts
|

Improved Recovery After Cold Crystalloid Cardioplegia Using Low-Dose Glutamate Enrichment During Reperfusion After Aortic Unclamping: a Study in Isolated Blood-Perfused Pig Hearts

Abstract: Increased glutamate utilization is a part of the metabolic adaptation to oxygen deprivation by the heart. The effect of low-dose L-glutamate (2 mmol/L) during continuous reperfusion after aortic unclamping on postcardioplegic recovery was studied in pig hearts similar in size, anatomy, and function to the human adult heart. After cold crystalloid cardioplegic arrest (CCC) with Bretschneider solution no 3, hearts were excised from pigs weighing 70-80 kgs (heart weight, average +/- SEM: 308 +/- 4 grams), and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…21 In addition, we have demonstrated that glutamate enrichment during reperfusion improves postcardioplegic recovery. 22 In the present study, captopril induced a massive glutamate release during postcardioplegic reperfusion. We have previously observed a substantial loss of glutamate from pig hearts at the start of reperfusion after cold crystalloid cardioplegia.…”
Section: Discussionsupporting
confidence: 48%
“…21 In addition, we have demonstrated that glutamate enrichment during reperfusion improves postcardioplegic recovery. 22 In the present study, captopril induced a massive glutamate release during postcardioplegic reperfusion. We have previously observed a substantial loss of glutamate from pig hearts at the start of reperfusion after cold crystalloid cardioplegia.…”
Section: Discussionsupporting
confidence: 48%